2013
DOI: 10.7150/ijbs.5996
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Receptor Blockade Selectively Reduces IL-21 Production by CD4 T Cells and IgG4 Autoantibodies in Rheumatoid Arthritis

Abstract: Interleukin-6 (IL-6) levels are known to be increased in patients with rheumatoid arthritis (RA). Tocilizumab, a monoclonal antibody to the IL-6 receptor (IL-6R), reduces disease activity in RA, although its mechanisms of action remain unclear. Since IL-6 regulates cytokine production by CD4 T cells during activation, we investigated whether treatment with tocilizumab altered the phenotype and cytokine production by CD4 T cells in patients with rheumatoid arthritis. We show here that tocilizumab treatment does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 55 publications
0
49
0
Order By: Relevance
“…However, recent preliminary results indicate that tocilizumab treatment can correct the imbalance between Th17 and Treg in peripheral blood CD4 þ T cells (Samson et al 2012;Pesce et al 2013). Moreover, it was shown that the treatment caused a reduction in the level of serum IgG4-class anticyclic citrullinated peptide Ab in RA (Carbone et al 2013). Anti-aquaporin 4 (AQP4) Ab plays a pathological role in neuromyelitis optica, and tocilizumab treatment was found to improve clinical symptoms and reduce serum anti-AQP4 Ab titers, perhaps by inhibiting cell survival of the plasmablasts secreting this Ab (Chihara et al 2011;Araki et al 2013).…”
Section: Il-6 In Inflammation Immunity and Diseasementioning
confidence: 99%
“…However, recent preliminary results indicate that tocilizumab treatment can correct the imbalance between Th17 and Treg in peripheral blood CD4 þ T cells (Samson et al 2012;Pesce et al 2013). Moreover, it was shown that the treatment caused a reduction in the level of serum IgG4-class anticyclic citrullinated peptide Ab in RA (Carbone et al 2013). Anti-aquaporin 4 (AQP4) Ab plays a pathological role in neuromyelitis optica, and tocilizumab treatment was found to improve clinical symptoms and reduce serum anti-AQP4 Ab titers, perhaps by inhibiting cell survival of the plasmablasts secreting this Ab (Chihara et al 2011;Araki et al 2013).…”
Section: Il-6 In Inflammation Immunity and Diseasementioning
confidence: 99%
“…IL-21 promotes plasma cell differentiation and preferentially induces IgG4 production [ 9 ]. One study demonstrated that tocilizumab treatment causes a selective reduction in IL-21 production of memory/activated T cells, leading to a reduction in the serum levels of IgG4-specifi c anti-citrullinated peptide Ab in RA patients [ 69 ]. Several recent reports demonstrated that tocilizumab therapy led to an increase in the number of Treg cells in peripheral blood CD4 + T cell fractions in RA patients [ 70 -72 ] (Fig.…”
Section: Mechanisms Through Which Tocilizumab Is Effi Cacious In Varimentioning
confidence: 99%
“…Tocilizumab also inhibits IgG4 (not IgG1)-class anti-CCP antibodies by blocking the effects of IL-6 on IL-21 production induced by CD4-T-cells (6). IL-6 exhibits ambivalent effects with respect to inflammation and neurotrophic repair depending on the pathological context in the central nervous system (CNS) (7).…”
Section: The Microscopic Findings Of the Obtained Tissue Showed Definmentioning
confidence: 99%